KEPEMIMPINAN KOLABORATIF DALAM MENINGKATKAN KETERLIBATAN ORANG TUA PADA PENDIDIKAN ANAK USIA DINI - Anisa Alsa Alfika Rohmah; Mega Nur Septianingrum; Nia Alfi Fauziah; Ulli Nikmah Salsabila; Siswadi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research arose from the low level of parental involvement in early childhood education (PAUD), despite their crucial role in supporting optimal child development. One effort to increase this involvement is to implement collaborative leadership in PAUD institutions. This study aims to analyze the concepts, forms, and strategies of collaborative leadership to increase parental involvement. The method used was a qualitative approach in the form of library research, collecting, reviewing, and synthesizing various relevant sources such as scientific journals, books, and previous research findings. The results of the study indicate that collaborative leadership plays a crucial role in building open communication, harmonious relationships, and trust between schools and parents. Forms of parental involvement include participation in school activities, active communication with teachers, and home learning support. Effective strategies to increase parental involvement include parenting programs, intensive communication, and direct involvement in school activities. However, their implementation faces challenges such as low parental awareness, limited time, and differences in socio-economic backgrounds. Therefore, a flexible, communicative, and sustainable approach is needed for optimal collaborative leadership. In conclusion, collaborative leadership has been shown to increase parental involvement and positively impact the overall development of early childhood.